2023
DOI: 10.1111/nph.18814
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome‐scale genome assembly and insights into the metabolome and gene regulation of leaf color transition in an important oak species, Quercus dentata

Abstract: Summary Quercus dentata Thunb., a dominant forest tree species in northern China, has significant ecological and ornamental value due to its adaptability and beautiful autumn coloration, with color changes from green to yellow into red resulting from the autumnal shifts in leaf pigmentation. However, the key genes and molecular regulatory mechanisms for leaf color transition remain to be investigated. First, we presented a high‐quality chromosome‐scale assembly for Q. dentata. This 893.54 Mb sized genome (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Anthocyanin biosynthesis is a branch of the avonoid synthesis pathway starting from phenylalanine, and involving a variety of enzymes encoded by early biosynthesis genes (PAL, 4CL, C4H, CHS, CHI, F3H, F3'H, and F3'5'H) and anthocyanin biosynthesis genes (DFR, ANS, and UFGT) [39]. Previous studies have shown that several key genes and enzymes are required for anthocyanin accumulation and leaf colour formation in many ornamental plants, such as Quercus dentata [40] and cassava (Manihot esculenta) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin biosynthesis is a branch of the avonoid synthesis pathway starting from phenylalanine, and involving a variety of enzymes encoded by early biosynthesis genes (PAL, 4CL, C4H, CHS, CHI, F3H, F3'H, and F3'5'H) and anthocyanin biosynthesis genes (DFR, ANS, and UFGT) [39]. Previous studies have shown that several key genes and enzymes are required for anthocyanin accumulation and leaf colour formation in many ornamental plants, such as Quercus dentata [40] and cassava (Manihot esculenta) [41].…”
Section: Discussionmentioning
confidence: 99%
“…The first published oak genome was that of Quercus robur (Plomion et al ., 2016a), the pedunculate oak, which is common throughout western Eurasia. To date, there have been at least nine Quercus species with published chromosome-scale genomes, including four annotated genomes from the white oak clade (Plomion et al ., 2016a; Han et al ., 2022; Liu et al ., 2022; Sork et al ., 2022; Zhou et al ., 2022; Ai et al ., 2022; Kapoor et al ., 2023; Wang et al ., 2023). This growing number of annotated genomes allows for comparative analyses of gene content and inferences of genome evolution across the oak phylogeny.…”
Section: Introductionmentioning
confidence: 99%
“…As an important ecological and economic tree in East Asia, oaks are famous for their environmental adaptability, resistance to biotic and abiotic stresses, and providing many biological materials [ 35 , 36 ]. Currently, eight chromosome-level oak genomes have been sequenced and annotated, including Q. acutissima [ 37 ], Q. dentata [ 38 ], Q. gilva [ 39 ], Q. glauca [ 40 ], Q. lobata [ 41 ], Q. mongolica [ 42 ], Q. robur [ 11 ], and Q. variabilis [ 43 ]. These provide a comprehensive database for analysing the genomic and chromosomal evolution of the genus.…”
Section: Introductionmentioning
confidence: 99%